Radiofrequency intervention methods in the treatment of pelvic pain - К. С. Новакович; Б. Б. Павлов (Publishing House TRILIST, 2017)
The article illuminates a general problem of a pelvic pain. This problem is resolving not only by gynecologists, proctologist, general surgeons, etc., but also neurosurgeons. Neurosurgeons have an experience of working on neural structures, responsible for the innervation of the pelvic organs, and also have the equipment that gives a possibility to perform a series of interventions. The complexity of diagnosis and treatment is caused by the proximity of anatomical and physiological kinship, blood supply and innervation of the pelvic organs. Hereby we give a clinical case to case: the patient, who started a treatment in clinic of Pain Medicine Center (Kyiv) after unsuccessful and prolonged attempt of conservative treatment. Main complains were about the pain in the tailbone, under the buttocks and lower back. The patient was diagnosed chronic perineal pain, protrusion of the disc L3-L4, severe arthropathy of facet joints, spinal stenosis at L3-L4. Chronic perineal pain was not associated with the pathology of internal organs, and the protrusion stenosis caused less pronounced as compared to perineal, and lumbar pain. This clinical case needed staged treatment which performed by epidural blockades, closures and radicular finally, RF techniques. Destruction or neyrolizys used to treat osteoarthritis facet joints, as well as perineal pain. To exclude the motor unit (with radiculopathy) used pulsed radiofrequency. Methods are self-sufficient, but it is complementary to be effective in the treatment of pelvic pain, in this clinical case having not one but several reasons. A sign that the treatment has been completed successfully - a positive therapeutic effect in a sustained and prolonged absence of pain after the last procedure. As the authors of the article notes, the success of the treatment of pelvic pain lies precisely in such a consistent approach from less complex steroid blockades to destructive radio-frequency procedures, taking into account the features of the course of the disease in each individual case.